Penerapan Metode Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Materi Mahluk Hidup - Firdausi, Rofiqoh; Albar, Melani (TARBAWIYAT, 2024)
In general, class 4 learning at MI Manarul Huda Sukoanyar Wajak. In general, students also tend to be passive and less active in learning, only accepting what the teacher says without being able to express opinions, ask and answer questions. If the teacher asks questions, students don't dare to answer. If there are problems students don't dare to ask. The formulation of the problem in this research is (1) How is the implementation of the STAD type cooperative learning method for class IV students at MI Manarul Huda in mastering the material "Living Creatures" (2) How to increase student learning activity in using the STAD type cooperative learning method in the material "Creatures Lifeâ€ The type of research used in this research is Classroom Action Research (PTK). The PTK model used is the kemmis and tagart model. The researcher carried out two cycles, namely cycle I and cycle II. The results of the research can be seen that student learning outcomes have increased from the initial test, the final test of cycle I, to the final test of cycle II. This can be seen from the average student score of 50 (initial test) with a percentage of 20%, increasing to 80 (final test of cycle I) with a percentage of 68%, and increasing again to 85 (final test of cycle II) with a percentage of 88%.